Illness and "daño". Etiology and treatment of smallpox among native societies of Araucanía (late 18th century) - Jiménez, Juan Francisco; Alioto, Sebatián L. (Revista Complutense de Historia de América, 2014)
In the year of 1791, a smallpox epidemic which affected the Indian populations of the Arauco frontier –south of Bío-Bío river in Chile– worried the colonial authorities of Concepción, due to the fear that the Spanish inhabitants of that region could also get infected. Acting according to the contagion paradigm, they imposed a cordon sanitaire in order to isolate them from the Natives, and suggested these do the same. Also, conscious that the plague was commonly attributed to Spanish witchcraft, they hurried to offer medicine and medical advice, in order to show there was no will to cause damage. The responses of the different Indian groups demonstrated the co-existence of a wide variety of perspectives regarding the etiology of smallpox and the possible paths of action: from a personalist conception which attributed it to witches’ activities, to the admission of their own inability to find proper treatment, which led to the acceptance of Spanish medicines. The general picture shows a native model of the illness that is both conservative and innovative, complex and dynamic at the same time. The description of those events, found in a folder which was later sent to Spain, and the references contained in other colonial documents, allow the examination of the epidemiologic event using as a comparative context the conceptualizations now current among the Mapuche. They also allow the analysis of dominant conceptions concerning illness among the Spaniards in the late eighteenth century.
Keywords: Smallpox; Indians; Etiology; Contagion; Witchcraft; Isolation; Therapies; Frontier; Chile; 18th Century.